Anticardiolipin and anti-beta2-glycoprotein-I antibodies in preeclampsia - Lee, Richard M; Brown, Melissa A; Branch, D Ware; Ward, Kenneth; Silver, Robert M (Obstetrics and gynecology (New York. 1953), 2003)
To estimate whether antiphospholipid antibodies, specifically anticardiolipin and anti-beta(2)-glycoprotein-I antibodies, are associated with preeclampsia. Plasma was prospectively obtained from four groups of pregnant women: those with 1) mild preeclampsia (n = 109); 2) severe preeclampsia (n = 134); 3) hemolysis, elevated liver enzymes, low platelets (HELLP) syndrome (n = 57); and 4) normotensive controls (n = 100). Anticardiolipin and anti-beta(2)-glycoprotein-I levels were determined by enzyme-linked immunoassay. Subjects with mild preeclampsia, severe preeclampsia, and HELLP syndrome did not have significantly elevated levels of immunoglobulin G (IgG) and IgM anticardiolipin and anti-beta(2)-glycoprotein-I antibodies compared with normotensive controls (P >.05, Kruskal-Wallis). Similarly, subjects with mild preeclampsia, severe preeclampsia, and HELLP syndrome did not have a significantly higher proportion of women testing positive for each autoantibody compared with normotensive controls (chi(2)). The proportion of patients testing positive for anticardiolipin and anti-beta(2)-glycoprotein-I antibodies were similar in patients with preeclampsia developing before and after 34 weeks' gestation (chi(2)). Circulating levels of both anticardiolipin and anti-beta(2)-glycoprotein-I antibodies were not increased in patients with mild preeclampsia, severe preeclampsia, or HELLP syndrome compared with normotensive controls. Our data do not support routine testing for anticardiolipin and anti-beta(2)-glycoprotein-I antibodies in women with preeclampsia.